Comparison of distal and proximal centralising devices in hip arthroplasty - (:unkn) unknown (SPRINGER, 2009)
Centralising devices were introduced to ensure that the prosthesis is implanted in a neutral position and that a cement mantle of optimal thickness is achieved proximally and distally. A distal centralising device (DCD) is compared with a proximal midshaft centralising device (PCD) to test which one provides a more neutral prosthetic alignment. Thirty consecutive patients undergoing hemiarthroplasties for femoral neck fractures were studied prospectively. Patients were blindly randomised to receive either a femoral component with proximal midshaft centraliser or distal centraliser. Both components were implanted following the manufacturer's protocol. Postoperative true anteroposterior and lateral radiographs were made to assess the stem position. There was no statistically significant difference between the two groups in zones 1, 2, 3, 4, 5, 6 and 7 in both anteroposterior and lateral radiographic measurements. DCP and PCD both have similar centralisation and cement mantle. Future studies should be done to evaluate their long-term effect.
Keywords: CEMENT MANTLE THICKNESS; RADIOGRAPHIC ANALYSIS; FEMORAL COMPONENTS; REPLACEMENT; FAILURE